Nurses' mental health from early COVID‐19 pandemic to vaccination. Issue 4 (30th December 2021) - Kim, Son Chae; Rankin, Larry; Ferguson, Jennifer
Abstract: Aims: The influence of the COVID‐19 vaccine and the evolution of the pandemic over time on nurses' mental health have not been thoroughly examined. This study aimed to explore the changes in nurses' mental health from the early pandemic to the early vaccination period over a 1‐year time span and examine vaccination and coping mechanisms as predictors of nurses' poor mental health and burnout. Methods: Three cross‐sectional surveys were conducted: Early‐pandemic ( n = 320), pre‐vaccination ( n = 228), and early‐vaccination cohorts ( n = 292). Findings: About 72% of nurses in the early‐vaccination cohort were fully vaccinated with two doses of mRNA COVID‐19 vaccines. There were significant decreases in moderate/severe anxiety and moderate/severe depression for the early‐vaccination cohort compared to the other cohorts. In multivariate analyses, vaccination had almost three‐fold higher odds of moderate/severe anxiety (Odds Ratio [OR] = 2.87; 95% Confidence Interval [CI] = 1.28–6.44). High resilience, family functioning, and spirituality were associated with two‐ to five‐fold lower odds of poor mental health and burnout. Conclusions: Although nurses in the early‐vaccination cohort had lower anxiety and depression than earlier cohorts, COVID‐19 vaccination had minimal associations with nurses' mental health. Coping mechanisms and organizational support appear to be important predictors of nurses' poor mental health and burnout. Clinical relevance: The evidence gathered over 1 year of the pandemic may be helpful for a better understanding of the challenges facing frontline nurses and preparing for future healthcare crises. As a part of the preparedness plan for the future, evidence‐based interventions that raise frontline nurses' resilience, as well as family and spiritual support, should be considered.